Pembentukan Karakter Melalui Lagu Dolalan pada Mata Pelajaran Bahasa Jawa - Arif Muzayin Shofwan Shofwan; Gandes Nurseto (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Character building in students can be done through a variety of subjects delivered by the teacher. This qualitative research using a case study describes the dolanan song in Javanese language subjects which is used to shape the character of students at MI Miftahul Huda Papungan 01 Blitar. The findings in this study, among others: First, the dolanan song functions as a medium to convey moral values ​​to students, such as obedience to religious teachings, love for the homeland and nation, togetherness, cooperation, and others; Second, there are dolanan songs that contain educative value and vice versa, a teacher must choose dolanan songs that contain educational values ​​for students; Third, several songs that can be found in this research, among others: Cublak-Cublak Suweng, Menthog-Menthog, Kidang Talun, Tikus Buntung, Gotri, and others; Fourth, most students feel happy and excited when singing the dolanan song because the song can be sung while playing (dolanan). Dolanan songs can also be used as an alternative to relieve tension in students when they are bored with thinking activities.